Acceptance and awareness of COVID-19 vaccine among healthcare professionals and students in India. A questionnaire based study - Meenakshi Upadhyay; Ankit Mahajan; Santosh K. Subudhi; Mohina Aggarwal; Madhura Pawar; Guna Shekhar (Journal of Family Medicine and Primary Care)
Background: The availability of vaccines against SARS-CoV-2 has met with reports of variations in knowledge concerning it, awareness as well as precipitation of the same in health professionals as well as the common public. Aim: This study aimed to evaluate knowledge, acceptance, and precipitation of COVID-19 vaccination among dental students as well as practitioners in India. Materials and Methods: This cross-sectional and observational questionnaire-based survey was conducted on 100 Dentistry students and 100 Dental practitioners. Inclusion criteria were a) age equal or above 18 years, b) individuals with familiarity with internet usage and social media sites; c) English language proficiency, and d) Voluntary participation. Exclusion criteria were a) students of other professional courses; b) other health-care professionals; c) no willingness to participate and d) Non-responsive subjects. Statistical Analysis: Responses obtained were statistically evaluated by SPSS software Version 21.0. Descriptive statistical analysis was performed for frequency, percentages, mean, and standard deviation computation. Pearson’s ‘Chi-Square’ and Fisher’s Exact Tests were used for the level of significance (P < 0.05). Results: All subjects had the knowledge and were aware of vaccination. However, there were a few misconceptions regarding the vaccine constitution. Precipitation (acceptance) was high in this study. Conclusion: A larger and wider sample distribution must be examined for a full understanding of the mindset of the targeted population.